2016
DOI: 10.1088/1748-3190/11/4/046002
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-steady aerodynamic model of clap-and-fling flapping MAV and validation using free-flight data

Abstract: Flapping-wing aerodynamic models that are accurate, computationally efficient and physically meaningful, are challenging to obtain. Such models are essential to design flapping-wing micro air vehicles and to develop advanced controllers enhancing the autonomy of such vehicles. In this work, a phenomenological model is developed for the time-resolved aerodynamic forces on clap-and-fling ornithopters. The model is based on quasi-steady theory and accounts for inertial, circulatory, added mass and viscous forces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 64 publications
(196 reference statements)
0
45
0
Order By: Relevance
“…The wing beat was assumed to be sinusoidal. While in the considered FWMAV the outstroke is slightly slower than the instroke, 12 this difference is small and was considered negligible, 12 particularly in view of the simplified nature of the aerodynamic model itself. More accurate mathematical representations of the kinematics, e.g., using a split-cycle piecewise representation, 37 or different functions such as the hyperbolic tangent would have increased the model complexity and interpretability, and are left for future work.…”
Section: Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wing beat was assumed to be sinusoidal. While in the considered FWMAV the outstroke is slightly slower than the instroke, 12 this difference is small and was considered negligible, 12 particularly in view of the simplified nature of the aerodynamic model itself. More accurate mathematical representations of the kinematics, e.g., using a split-cycle piecewise representation, 37 or different functions such as the hyperbolic tangent would have increased the model complexity and interpretability, and are left for future work.…”
Section: Assumptionsmentioning
confidence: 99%
“…Significant effort has been spent on developing accurate aerodynamic models, particularly ones that are not excessively complex and can be applied for design, simulation and control. In an application context, the most widely used approach for this is quasi-steady modelling, [8][9][10][11][12] and, to a lesser extent, data-driven modelling. [13][14][15][16][17][18] However, the combination of wings and tail has not been widely studied, despite being used on many flapping-wing robots; instead the design of the tail in such vehicles so far has largely relied on an engineering approach.…”
Section: Introductionmentioning
confidence: 99%
“…eqs. [8][9][10][11][12][13][14][15][16][17][18][19] were found to converge in the static case, while during flight they vary to a limited extent, typically in conjunction with maneuvers. It can for instance be observed in fig.…”
Section: A Fusion Resultsmentioning
confidence: 93%
“…consid- ering the effect of the flapping-related oscillations in the states, however it is particularly essential in aerodynamic studies. It has for instance been shown that some unsteady effects, such as clapand-fling, are visible clearly only at very high frequencies [14], which are typically only accurately observable in wind tunnel tests. At the same time, as mentioned in sec.…”
Section: B Outlook For Time-resolved Flapping Flight Analysismentioning
confidence: 99%
See 1 more Smart Citation